Synthesis of Au50Ag50 Alloy Nanoparticles From Metal Ions and Colloidal Nanoparticles Through Photochemical Reduction Methods Using Femtosecond Laser: Affi Nur Hidayah, Yuliati Herbani - Affi Nur Hidayah Affi Nur Hidayah; Yuliati Herbani Yuliati Herbani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
Nanoparticles synthesized through photochemical reduction using femtosecond involve reducing agent that reduces metal ions into nanoparticles. We synthesized Au50Ag50 from metal ions and colloidal nanoparticles in four different conditions: (i) gold metal ions and silver metal ion, (ii) colloidal gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs), (iii) gold metal ions and colloidal silver nanoparticles (AgNPs), and (iv) colloidal gold nanoparticles (AuNPs) and silver metal ions. Gold and metal ions were obtained from dilution of gold and silver metal salts. While gold and silver nanoparticles were obtained from gold and metal ions added into a quartz cuvette and irradiated by femtosecond laser in 10 minutes irradiation time. In the synthesis, every condition respectively mixed in 3 ml solution into a 10x10x45 mm quartz cuvette and irradiated by femtosecond laser in 5-, 10- and 15- minutes irradiation time. The result showed that Au50Ag50 alloy nanoparticles were successfully synthesized in four different conditions, and the LSPR (Localized Surface Plasmon Resonance) in 15 minutes irradiation time was observed at 454.51, 458.74, 459.60, and 457.29 nm in the condition (i), (ii), (iii), and (iv), respectively.